The effect of negative incentives in an student evaluation of teaching online system - Cid-Cid, Ana I.; Leguey, Santiago; Prieto, Jaime; Guede-Cid, Rocío (Revista Complutense de Educación, 2025)
Several studies have shown that online administration of Students’ Evaluation of Teaching (SET) surveys typically results in significantly lower response rates compared to paper-based administration conducted in the classroom. To address this issue, institutions have implemented various incentives as extrinsic motivators for students, either of positive (e.g., early release of grades) or negative nature (e.g., making survey completion a prerequisite for accessing exam results). This study aimed to analyze the impact of introducing a negative incentive (requiring students to complete the survey in order to access their grades) on the response rates of SET surveys during a university’s transition from a paper-based system (without incentives) to an online one. The analysis covered teaching evaluations from 35,497 course subjects across 18 semesters, with nine semesters using paper surveys administered in class and the other nine using online surveys. The main findings of the study showed that the introduction of the incentive contributed to higher response rates but also led to undesirable effects, such as an increased number of students providing uniform responses across all survey items. These results suggest a possible lack of genuine engagement, with students completing surveys hastily and with minimal effort solely to access their grades. The study discusses the implications of these findings and offers recommendations for university administrators regarding the design and implementation of SET survey strategies.